Diagnosis of 7q11.23 deletion in a patient from Manaus, Amazonas with Williams-Beuren syndrome: Case report (Research, Society and Development, 2024)
Williams-Beuren Syndrome is a rare disease caused by a chromosomal microdeletion in region 7q11.23.  It is characterized as multisystemic, including intellectual and learning disabilities, distinct facial features, short stature, hypersocial behavior, and many malformations. Its diagnosis is traditionally clinical, but cytogenomic analyses such as fluorescence in situ hybridization can also be used for better etiological characterization of the syndrome. Our objective is to report the case of a boy in Manaus/Amazonas with Williams-Beuren Syndrome that presents a microdeletion in region 7q11.23. The patient is male, 12 years, of non-consanguineal parents, and no family history of hereditary diseases. The patient was sent for genetic testing after assessment of possible genetic syndrome, as the physical exams presented a gnome-like face, short nasal bridge, full lips, frequent smile, short stature, difficulty learning and atrioventricular dysplasia of valves with mild insufficiency and a cist in the left kidney. The results of the karyotype exam were normal and the fluorescence in situ hybridization revealed the microdeletion of region 7q11.23. Upon the follow-up, the subject was diagnosed with Williams-Beuren Syndrome. This microdeletion results in the loss of various genes that affect genic dosage/genic haploinsufficiency, resulting in a cytogenetic imbalance, consequently contributing to the patient’s phenotype. Therefore, the cytogenomic analysis was instrumental for the etiological diagnosis, in which microdeletion 7q11.23 was identified, allowing for proper diagnosis and prognosis, genetic counseling, and medical decisions, granting a better quality of life for the patient.